Preservation of Gastrointestinal Mucosal Barrier Function and Microbiome in Patients With Controlled HIV Infection - Mak, Gerald; Zaunders, John J.; Bailey, Michelle; Seddiki, Nabila; Rogers, Geraint; Leong, Lex; Phan, Tri Giang; Kelleher, Anthony D.; Koelsch, Kersten K.; Boyd, Mark A.; Danta, Mark (Frontiers in Immunology, 2021)
Background: Despite successful ART in people living with HIV infection (PLHIV) they experience increased morbidity and mortality compared with HIV-negative controls. A dominant paradigm is that gut-associated lymphatic tissue (GALT) destruction at the time of primary HIV infection leads to loss of gut integrity, pathological microbial translocation across the compromised gastrointestinal barrier and, consequently, systemic inflammation. We aimed to identify and measure specific changes in the gastrointestinal barrier that might allow bacterial translocation, and their persistence despite initiation of antiretroviral therapy (ART). Method: We conducted a cross-sectional study of the gastrointestinal (GIT) barrier in PLHIV and HIV-uninfected controls (HUC). The GIT barrier was assessed as follows: in vivo mucosal imaging using confocal endomicroscopy (CEM); the immunophenotype of GIT and circulating lymphocytes; the gut microbiome; and plasma inflammation markers Tumour Necrosis Factor- (TNF-) and Interleukin-6 (IL-6); and the microbial translocation marker sCD14. Results: A cohort of PLHIV who initiated ART early, during primary HIV infection (PHI), n=5), and late (chronic HIV infection (CHI), n=7) infection were evaluated for the differential effects of the stage of ART initiation on the GIT barrier compared with HUC (n=6). We observed a significant decrease in the CD4 T-cell count of CHI patients in the left colon (p=0.03) and a trend to a decrease in the terminal ileum (p=0.13). We did not find evidence of increased epithelial permeability by CEM. No significant differences were found in microbial translocation or inflammatory markers in plasma. In gut biopsies, CD8 T-cells, including resident intraepithelial CD103+ cells, did not show any significant elevation of activation in PLHIV, compared to HUC. The majority of residual circulating activated CD38+HLA-DR+ CD8 T-cells did not exhibit gut-homing integrins 4ß7, suggesting that they did not originate in GALT. A significant reduction in the evenness of species distribution in the microbiome of CHI subjects (p=0.016) was observed, with significantly higher relative abundance of the genus Spirochaeta in PHI subjects (p=0.042). Conclusion: These data suggest that substantial, non-specific increases in epithelial permeability may not be the most important mechanism of HIV-associated immune activation in well-controlled HIV-positive patients on antiretroviral therapy. Changes in gut microbiota warrant further study.